Reformas a la ley forestal y de conservación de áreas naturales y vida silvestre en cuanto a que las sanciones sean mayores a las establecidas para las personas que se dedican a la deforestación y daños naturales. - Sigcho Gualán, César Jhonn (2014)
The development of this research prior to obtaining a law degree, revolves around the problems arising from the improper or unauthorized manipulation of plant and tree species This research aims to conduct a thorough legal, doctrinal and critical analysis on the improper or unauthorized handling plant and forest species, this activity brings imbalance and environmental pollution. Through the development of theoretical and empirical content has been achieved infer that currently, although the State recognizes nature as a somebody and not as something that can explode and destroy, giving him the right to be fully in respect its existence, maintenance and regeneration of its vital cycles, structure, functions and evolutionary processes; the development of secondary legislation is insufficient to protect the environmental legal right, because there are specific rules whose content is meager; I refer specifically to Article 78 de la Ley Forestal y de Conservación de Áreas Naturales y Vida Silvestre, where severe penalties for offenders forest down . Furthermore, the development of research expose what prescribed by international laws and mandatory for the Ecuadorian government as a signatory , in which environmentally harmful behaviors are prohibited, as is, environmental deforestation Finally, this work is corroborated by performing a field study based on the problem investigated, to what has been obtained the judgment of a group of professionals in the legal sciences through technical survey and interview, who have expressed their views and opinions regarding the proposed theme, suggesting incorporate legal reforms to Article 78 de la Ley Forestal y de Conservación de Áreas Naturales y Vida Silvestre.